Comparison of rArt v 1-based sublingual and subcutaneous immunotherapy in a murine model of asthma - Tabynov, Kairat; Tailakova, Elmira; Rakhmatullayeva, Guliza; Bolatbekov, Turlan; Lim, Yeow Hong; Fomin, Gleb; Babayeva, Meruert; Valenta, Rudolf; Tabynov, Kaissar (Nature Research, 2025)
Mugwort-allergic patients frequently experience severe respiratory allergies due to sensitization to the major allergen Art v 1, with allergen-specific immunotherapy (ASIT) as the only causal treatment to halt disease progression. This study evaluated the effects of subcutaneous (SCIT) and sublingual (SLIT) ASIT with purified recombinant Art v 1 (rArt v 1) in a murine model of mugwort pollen of asthma. BALB/c mice were sensitized with Artemisia vulgaris pollen extract and treated with either rArt v 1-based SCIT adjuvanted with Montanide ISA-51, rArt v 1-based SLIT, an extract-based commercial SLIT vaccine, or PBS. Both rArt v 1-based SCIT and SLIT improved lung pathology and reduced airway reactivity following allergen challenge, with rArt v 1-based SCIT inducing Th1-polarized immune responses marked by increased IFN-γ production and rArt v 1-specific IgG1/IgG2a, while SLIT induced stronger mucosal IgA responses. These findings highlight the therapeutic potential of rArt v 1-based ASIT for mugwort allergy.